2010
DOI: 10.4028/www.scientific.net/amr.173.106
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Co-Cr-Mo (F-75) Alloy Produced by Solid State Sintering

Abstract: This research was carried out to fabricate and characterize Co-Cr-Mo (F-75) alloy. The samples have been prepared via solid state sintering. The lab work comprises the mixing of F-75 alloy powder with 2 wt. % of binder. The mixture was cold compacted using uniaxially press at 500 MPa. The samples were sintered at three different temperatures (1250 °C, 1300 °C and 1350 °C) in inert environment for 90 minutes of sintering time. The sintered samples were characterized by using Scanning Electron Microscope (SEM), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
1
1
Order By: Relevance
“…This fact leads to porosity reduction and automatically affects hardness. The hardness result from our samples is greater than that obtained from Zuraidawani Che Daud et al [16]. The highest rate in terms of porosity is obtained from a sample sintered at 1200°C.…”
Section: Density Evolution and Microhardnesscontrasting
confidence: 72%
“…This fact leads to porosity reduction and automatically affects hardness. The hardness result from our samples is greater than that obtained from Zuraidawani Che Daud et al [16]. The highest rate in terms of porosity is obtained from a sample sintered at 1200°C.…”
Section: Density Evolution and Microhardnesscontrasting
confidence: 72%
“…Suresh et al [17] have reported that the iron powders with an average particle size in the range of 2 to 150 microns show a linear relationship between green density and pressure. Daud et al [18] have reported that the grains and bulk density increase with increasing sintering temperature and sintering times. However, opposite results were obtained for apparent porosity, hardness and compressive strength, while Dixit et al [10] have reported that the compaction pressure highly influences the pore size as well as the number of pores.…”
Section: Powder Metallurgy Super Hexagonmentioning
confidence: 99%